Analisis Linguistik terhadap Pembelajaran Bahasa dan Agama dalam Manuskrip Kuno Bainul Haq - Hasanuddin Chaer; Aswandikari Aswandikari; Muh. Syahrul Qodri; Murahim Murahim; Yunia Sari; Abdul Rasyad (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This research addresses the issue of cultural value transmission in the practice of Sufism through a linguistic approach to language and religious learning in the ancient manuscript Bainal Haq. The primary objective of this research is to identify the linguistic mechanisms involved in conveying Sufi teachings and preserving local Islamic and cultural values. This research employs a qualitative approach with text analysis, which involves several stages: (1) data collection from the ancient manuscript Bainal Haq, (2) determining the focus of analysis, which includes syntactic aspects (sentence structure and relationships between words) and semantic aspects (word meanings and their relation to Sufi teachings and culture), (3) data analysis, (4) interpretation of data based on Hans-Georg Gadamer’s hermeneutic theory, and (5) discussion related to relevant literature. The findings reveal that the language structure in the manuscript reflects spiritual depth and serves as an effective medium for transmitting cultural and religious values. In conclusion, the ancient manuscript Bainal Haq plays a significant role in the inheritance of local Islamic spirituality, particularly in the practice of Sufism within the Sasak local tradition.